The hymenopterans associated with an agroforestry plot of Borojoa petinoi, Cedrela odorata, Apeiba aspera and Inga spectabilis at the farm of the University of Chocó, municipality of Lloró, Chocó - NEITA-M., JHON CÉSAR; CORTÉS-V., HERNÁN; MADRIGAL-C.J, ALEJANDRO (Revista Colombiana de Entomología, 2004)
This research was conducted on the farm of the "Universidad Technological del Chocó", municipality of Lloro, 90 elev. and 24ºC. Surveys were conducted over twelve months by periodically sampling each of the plant species selected; insects were directly captured from plant structures. The diversity of hymenopterans between forest and agricultural components was compared; in addition, the trophic groups for hymenopterans from each parcel were established. Forty species were identified, distributed in 8 families, with 57,5% of the species belonging to the family Formicidae; followed by Apidae with 17,5%, lchneumonidae with 10% and Vespidae with 5%; the remaining 10% belonged to Argidae, Braconidae, Mymaridae and Pompilidae. Borojoa patino had the highest diversity of Hymenoptera and Apeiba aspera the lowest. About 44,4% of the insect species were common to all four plant components. Among the phytophagous insects, nectar and pollen feeders were the most representative with 17,5% each. Among the entomophagous lnsects. predators predominated with 32,5%. The abundance of the insects was associated with the phenology of the plant species in the parcel. B. petinoi, Cedrella odorata and Inga spectabilis shared the same periods of regrowth and flowering between April and May, when the abundance of Hymenoptera and their natural enemies was highest. The most abundant species were E:ulaena meriana, Lestrimelitta limao (first reports for Chocó) and Sericomyrmex sp. (first report of the genus for Chocó). One economically important species, Atta cephalotes, was identified because of its damage to B. patinoi fruits.